1/3(x-2)=3x-2(x-1)+22/3

Simple and best practice solution for 1/3(x-2)=3x-2(x-1)+22/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3(x-2)=3x-2(x-1)+22/3 equation:


x in (-oo:+oo)

(1/3)*(x-2) = 3*x-(2*(x-1))+22/3 // - 3*x-(2*(x-1))+22/3

(1/3)*(x-2)+2*(x-1)-(3*x)-(22/3) = 0

(1/3)*(x-2)+2*(x-1)-3*x-22/3 = 0

1/3*(x-2)+2*(x-1)-3*x-22/3 = 0

(1/3*3*(x-2))/3+(2*3*(x-1))/3+(-3*3*x)/3-22/3 = 0

1/3*3*(x-2)+2*3*(x-1)-3*3*x-22 = 0

7*x-9*x-22-8 = 0

-2*x-22-8 = 0

-2*x-30 = 0

(-2*x-30)/3 = 0

(-2*x-30)/3 = 0 // * 3

-2*x-30 = 0

-2*x-30 = 0 // + 30

-2*x = 30 // : -2

x = 30/(-2)

x = -15

x = -15

See similar equations:

| 12-7x=-6x | | 3/4(3x+1)=4(1-3x)+11 | | 3/2(3x+3)=4(1-2x)+13 | | y=6b+3mx | | 8(2n+3)=6(7n+1)+6 | | x+4/4x=0 | | x^2+2x-12y+25=0 | | w/4-3=8 | | 4m-6=22 | | a/3+5=6 | | 2*9-5= | | 3/4x=1/8 | | 6(3x+2)=17x-18x | | 2*9-5=9+4 | | 2+y/3=5 | | 2(x+40)=3(x-2) | | 1+4g=13 | | 3z-4.5=4z | | f(x)=3x^2+5x+4 | | 10=.25x-8 | | 23x+23=4(5x+6)+3x-1 | | -16t^2+50t+5=0 | | 2x/56=7 | | w=p/2-l | | 14+ln(2x-10)=20 | | 5-x-2=3+4c+5 | | 50+50+50=550 | | (2+3i)/(8-7i) | | 10000=18.56+22.73 | | log(2)(x+3)+log(2)(x-1)=5 | | 3016.46x2/3 | | 3x^2-24x+49=0 |

Equations solver categories